I'dad Wasilah Ta'lim al-Mufradat 'Ala Asas Android bi-Istikhdami Mauqi' Kodular - Chamidah, Dewi; Fauzan, Ahyar; Bakheet, Bakri Muhammad (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
Android apps are one of the best language learning tools in this technological age. There are many successful researches in developing the process of teaching the Arabic language through these applications. This paper aims to describe how to set up an Android-based vocabulary learning tool using Kodular website, and measure its suitability for vocabulary learning. The researcher uses the Design Research approach with three steps: analyzing practical problems, developing solutions, and testing and improvements. Through the tests, we find that the level of applicability of the alpha test is 96.3%, and the level of applicability of the expert test is 86%. So we can say that this application is "very decent" to be used in a real education environment.